Approaches to Molecular Magnetic Materials from the Use of Cyanate Groups in Higher Oxidation State Metal Cluster Chemistry: Mn14 and Mn16. Issue 13 (21st March 2013) - Alexandropoulos, Dimitris I.; Papatriantafyllopoulou, Constantina; Li, Chaoran; Cunha‐Silva, Luís; Manos, Manolis J.; Tasiopoulos, Anastasios J.; Wernsdorfer, Wolfgang; Christou, George; Stamatatos, Theocharis C.
Abstract: The initial employment of cyanato groups in higher oxidation state manganese cluster chemistry, in conjunction with the gem‐diolate form of di‐2‐pyridylketone or 2, 6‐diacetylpyridine dioxime chelate ligands, has afforded structurally interesting Mn II/III 14 and Mn II/III/IV 16 clusters, respectively. In both complexes, the end‐on bridging cyanato groups show an obvious preference in binding through their O atom, a significantly different ligation than that for the homoatomic‐type N3 – ligand. The Mn14 compound shows entirely visible out‐of‐phase signals below 5 K and large hysteresis loops below 2 K. Abstract : The use of cyanato groups in higher oxidation state Mn cluster chemistry, in combination with the gem‐diolate form of di‐2‐pyridylketone or 2, 6‐diacetylpyridine dioxime chelate ligands, has afforded structurally new Mn14 and Mn16 clusters, respectively; the Mn14 compound shows entirely visible out‐of‐phase signals below 5 K and large hysteresis loops below 2 K.